Pengembangan Materi Ajar Berbantuan Edmodo pada Mata Pelajaran Gambar Teknik Manufaktur untuk SMK - Ervin Priambodo; Apri Nuryanto (Department of Mechanical Engineering Education, 2020)
This study aims to determine the process of developing Edmodo-assisted teaching materials and determine the level of eligibility in learning Manufacturing Engineering Drawings subject. The research type is Research and Development methods (R&D), using the 4D model, which consists of four steps, namely defining, design, development, and disseminating. The subjects of this study were 30 students of SMK N 2 Yogyakarta majoring in Machining. Data collection techniques are done by observation, interviews, and questionnaires. The initial analysis was done descriptively, while the feasibility data analysis was carried out quantitatively. The quantitative data were subsequently converted into qualitative data. These development results are (1) Edmondo-assisted teaching material products in Manufacturing Engineering Drawing (GTM) subjects with the flip builder application's help. The learning material is divided into five learning activities: drawing 2D sketches, making 3D drawings, editing 3D models, assembling 3D models (assembly), and making working drawings. (2) The feasibility of teaching materials and the media used is determined from the experts' validation results, with the results of the validation of the material experts 82% and 83.65% media experts, which are in the very feasible criteria. The revised product is then tested on students through online trials, with 83.105% results are in the very feasible category. In conclusion, the Edmodo-assisted teaching materials on Manufacturing Engineering Drawing subjects for Vocational Schools are very suitable for use in learning.Penelitian ini bertujuan untuk mengetahui proses pengembangan materi ajar berbantuan Edmodo dan mengetahui tingkat kelayakannya untuk diterapkan dalam pembelajaran Gambar Teknik Manufaktur (GTM). Jenis penelitian ini mengunakan metode penelitian dan pengembangan (Research & Development) dengan menggunakan model 4D yang terdiri dari empat langkah yaitu pendefinisian (define), perancangan (design), pengembangan (development), dan penyebarluasan (disseminate). Subjek penelitian ini adalah siswa SMK N 2 Yogyakarta jurusan Pemesinan kelas XII yang berjumlah 30 siswa. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan angket. Analisis awal dilakukan secara deskriptif, sedangkan analisis data kelayakan dilakaukan secara kuantitatif yang dikonversi ke dalam data kualitatif. Hasil pengembangan ini disampaikan sebagai berikut. (1) Produk materi ajar berbantuan Edmodo pada mata pelajaran GTM dengan bantuan aplikasi flip builder terbagi dalam 5 kegiatan pembelajaran, yaitu: menggambar sketch 2D, membuat gambar 3D, mengedit model 3D, merakit model 3D (assembly), dan membuat gambar kerja. (2) Kelayakan materi ajar dan media berdasarkan hasil validasi ahli materi 82% dan ahli media 83,65% sehingga termasuk pada kriteria sangat layak. Produk yang telah direvisi kemudian diujikan kepada siswa melalui uji coba secara online dengan hasil 83,105% yang termasuk dalam kategori sangat layak. Dengan demikian, ateri ajar berbatuan Edmodo pada mata pelajaran Gambar Teknik Manufaktur untuk SMK sangat layak digunakan dalam pembelajaran.